Modelling burning thermonuclear plasma - Rose,S; Hatfield,P; Scott,R (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2020)
Considerable progress towards the achievement ofthermonuclear burn using inertial confinement fusion has beenachieved at the National Ignition Facility (NIF) in the USA inthe last few years. Other drivers, such as the Z-machine atSandia, are also making progress towards this goal. A burningthermonuclear plasma would provide a unique and extremeplasma environment; in this paper we discuss a) differenttheoretical challenges involved in modelling burning plasmasnot currently considered, b) the use of novel machine learningbased methods that might help large facilities reach ignition,and c) the connections that a burning plasma might have tofundamental physics, including QED studies, and the replicationand exploration of conditions that last occurred in the first fewminutes after the Big Bang.